(3eYGgO GdJfUjU Ydi ThGgO GdJdNjUs - (3YHO GdQMje GdYHGSjs; (3eMeO Hf YHO GdQMef Hf YeQ, CHh GdeYGdj, LdGd GdOjf GdbRhjfj GdTGaYj, GdeYQha HNWjH OeTb,J (B739 (3g` s
(3ChdgG (B:s
(3dCMO Cf KdGK eQGJ eJhGdjGJ s
(3BNQgG (B:s
(3hgh ef bhd GHf GeYJR hGddg dG dcdeJgG s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3hYdjgG Jedc s
(3hgj eShOg GdeDda s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B192 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B145s
Keywords: (3GdHdGZIs